Optimal design of disks subject to geometric constraints - Kozłowski, W.; Mróz, Z. (International journal of mechanical sciences, 1970)
A general formulation of the problem of optimal design with geometric constraints is presented. Such constraints define an admissible region in which the variable portion of a structure should be placed. The optimal design of perfectly plastic disks of Tresca material is considered and two problems are discussed in detail: a disk simply supported at two points supports and a cantilever disk loaded by a concentrated force. The optimal design lies in the semi-plane below the line joining supports or within a strip of prescribed width.